2007
DOI: 10.1161/atvbaha.107.152462
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin Mediates the Suppressive Effect of Rosiglitazone on Plasminogen Activator Inhibitor-1 Production

Abstract: Objective-The purpose of this study was to examine the effects of PPAR-␥ agonist rosiglitazone, relative to sulfonylureas, on circulating levels of adiponectin and the prothrombotic factor, plasminogen activator inhibitor (PAI)-1, in type 2 diabetic patients, and to investigate, in animal models, whether the antithrombotic action of rosiglitazone was mediated through adiponectin. Methods and Results-Our clinical study (nϭ64) showed that after 24-week add-on therapy, the rosiglitazone group had a greater mean r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2008
2008
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 44 publications
1
20
0
Order By: Relevance
“…On day zero of the experiment, mice were randomized to receive vehicle (control), rosiglitazone (RSG, 20 mg/kg/day25, oral gavage, Cayman Chemical, Ann Arbor, Michigan), MnTE-2-PyP 5+ (a cell permeable SOD mimic, 10 mg/kg/day, IP27) or RSG+MnTE-2-PyP 5+ (to determine the possible involvement of superoxide in RSG cardiac signaling). Seventy two hours after the first drug administration, mice were anesthetized with 2% isoflurane, and myocardial ischemia (MI) was produced by temporarily exteriorizing the heart via a left thoracic incision, and ligation of the left anterior descending (LAD) coronary artery with a 6-0 silk suture.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On day zero of the experiment, mice were randomized to receive vehicle (control), rosiglitazone (RSG, 20 mg/kg/day25, oral gavage, Cayman Chemical, Ann Arbor, Michigan), MnTE-2-PyP 5+ (a cell permeable SOD mimic, 10 mg/kg/day, IP27) or RSG+MnTE-2-PyP 5+ (to determine the possible involvement of superoxide in RSG cardiac signaling). Seventy two hours after the first drug administration, mice were anesthetized with 2% isoflurane, and myocardial ischemia (MI) was produced by temporarily exteriorizing the heart via a left thoracic incision, and ligation of the left anterior descending (LAD) coronary artery with a 6-0 silk suture.…”
Section: Methodsmentioning
confidence: 99%
“…Treatment with PPARγ agonists stimulates APN production in adipocytes, and APN is the mediator through which PPARγ agonists achieve their insulin sensitization and metabolic benefits23. Moreover, recent experimental studies have demonstrated that APN plays an essential role in both the hepatic insulin sensitization and the plasminogen-activator-inhibitor-1 production suppressive effect of PPARγ agonists24,25. However, whether increased APN production as a result of PPARγ agonist treatment is solely an epiphenomenon, or is causatively related to PPAR-γ’s cardioprotective actions remains completely unknown.…”
mentioning
confidence: 99%
“…Adiponectin knock-out (ADN-KO) mice in C57BL/6J background and the leptin receptor (Lepr) −/− /adiponectin −/− double knockout (DKO) mice were generated as we described recently (19). UCP2 knockout (UCP2-KO) mice in C57BL/6J background were purchased from the Jackson Laboratory (Bar Harbor, ME).…”
Section: Methodsmentioning
confidence: 99%
“…101 in addition, administration of adiponectin inhibits Pai-1 production in 3t3-l1 adipocytes and adenovirus-mediated over expression of adipo nectin suppresses Pai-1 expression in diabetic db/db mice. 101 However, PParγ ligands increased Pai-1 mrna and protein expression in human endothelial cells. 108 the inhibition of Pai-1 expression by lipid-lowering agents perhaps occurs because lipoprotein induces Pai-1 upregula tion.…”
Section: Strategies For Inhibiting Pai-1mentioning
confidence: 99%